Environmental contamination with SARS‐CoV‐2 in nursing homes. Issue 1 (5th November 2021) - Mody, Lona; Gibson, Kristen E.; Mantey, Julia; Bautista, Liza; Montoya, Ana; Neeb, Karen; Jenq, Grace; Mills, John P.; Min, Lillian; Kabeto, Mohammed; Galecki, Andrzej; Cassone, Marco; et al.
Abstract: Background: SARS‐CoV‐2 outbreaks in nursing homes (NHs) have been devastating and have led to the creation of coronavirus disease 2019 (COVID‐19) units within NHs to care for affected patients. Frequency and persistence of SARS‐CoV‐2 environmental contamination in these units have not been studied. Methods: A prospective cohort study was conducted between October 2020 and January 2021 in four Michigan NHs. Swabs from high‐touch surfaces in COVID‐19‐infected patient rooms were obtained at enrollment and follow‐up. Demographic and clinical data were collected from clinical records. Primary outcome of interest was the probability of SARS‐CoV‐2 RNA detection from specific environmental surfaces in COVID‐19 patient rooms. We used multivariable logistic regression to assess patient risk factors for SARS‐CoV‐2 contamination. Pairwise Phi coefficients were calculated to measure correlation of site‐specific environmental detection upon enrollment and during follow‐up. Results: One hundred and four patients with COVID‐19 were enrolled (61.5% >80 years; 67.3% female; 89.4% non‐Hispanic White; 51% short stay) and followed up for 241 visits. The study population had significant disabilities in activities of daily living (ADL; 81.7% dependent in four or more ADLs) and comorbidities, including dementia (55.8%), diabetes (40.4%), and heart failure (32.7%). Over the 3‐month study period, 2087 swab specimens were collected (1896 COVID‐19 patient rooms, 191 common areas). SARS‐CoV‐2 positivity was 28.4% (538/1896 swabs) on patient room surfaces and 3.7% (7/191 swabs) on common area surfaces. Nearly 90% (93/104) of patients had SARS‐CoV‐2 contamination in their room at least once. Environmental contamination upon enrollment correlated with contamination of the same site during follow‐up. Functional independence increased the odds of proximate contamination. Conclusions: Environmental detection of viral RNA from surfaces in the rooms of COVID‐19 patients is nearly universal and persistent; more investigation is needed to determine the implications of this for infectiousness. Patients with greater independence are more likely than fully dependent patients to contaminate their immediate environment.